Boosting the Energy Density of Carbon‐Based Aqueous Supercapacitors by Optimizing the Surface Charge. (27th March 2017) - Yu, Minghao; Lin, Dun; Feng, Haobin; Zeng, Yinxiang; Tong, Yexiang; Lu, Xihong
Abstract: The voltage of carbon‐based aqueous supercapacitors is limited by the water splitting reaction occurring in one electrode, generally resulting in the promising but unused potential range of the other electrode. Exploiting this unused potential range provides the possibility for further boosting their energy density. An efficient surface charge control strategy was developed to remarkably enhance the energy density of multiscale porous carbon (MSPC) based aqueous symmetric supercapacitors (SSCs) by controllably tuning the operating potential range of MSPC electrodes. The operating voltage of the SSCs with neutral electrolyte was significantly expanded from 1.4 V to 1.8 V after simple adjustment, enabling the energy density of the optimized SSCs reached twice as much as the original. Such a facile strategy was also demonstrated for the aqueous SSCs with acidic and alkaline electrolytes, and is believed to bring insight in the design of aqueous supercapacitors.